Hans Blumenbergs “Objet ambigu” und Giorgio Agambens “Dispositiv”. Kongruenz zweier poetologischer Paradigmen in der Sprache der Lyrik (Studia theodisca, 2015)
This article discusses the idea of a specific lyric-theoretical power of language. Through Blumenberg’s pattern of the objet ambigu, it analyzes to what extent the performative character of the word can be seen as an ontological implication of its original linguistic potential. Through Agamben’s concept of the apparatus, it considers the «dispositive» character of the native power of self-determination of the word in the context of absolute semantic ambiguity. This is to clarify the sense in which the word, under precise conditions, is the authentic «power of the figure» and how the «apparatus»-concept allows a deeper understanding of poetry according to the paradigm of ambiguity.